Psychometric properties of the generalized anxiety disorder questionnaire (GAD-7) in a polish postpartum women sample - Karolina Lutkiewicz; Łucja Bieleninik; Paweł Jurek; Mariola Bidzan (BMC, 2024)
Abstract Objective Generalized Anxiety Disorder is an international mental health problem. Prevalence for anxiety disorders reported in perinatal period is high and related with adverse parental and child outcomes. Thus, the objective of this study was to investigate the psychometric properties and factorial validity of General Anxiety Disorder-7 questionnaire (GAD-7) in the context of postpartum mothers. Methods In this cross-sectional study, 278 mothers (mean age 31.09; SD = 4.42) were recruited at the Neonatology, Gynecology, and Obstetrics Ward. Generalized Anxiety Disorder was assessed with GAD-7, stress with Parental Stress Scale (PSS), while risk of depression with Edinburgh Postpartum Depression Scale (EPDS). Confirmatory factor analysis (CFA) was used to verify factor structure of GAD-7 and the internal consistency was evaluated using reliability coefficients: Cronbach's Alpha and McDonald's Omega. Results The internal consistency of the GAD-7 was high (Cronbach's Alpha = 0.90 and MacDonald's Omega = 0.91). GAD-7 had significant correlations with the variables examined for construct validity, stress (PSS; r = 0.35, p < 0.01) and risk of depression (EPDS; r = 0.76, p < 0.01). The Confirmatory Factor Analysis results supported a good fit of the data to the model: χ²(df) = 14.19 (14), p = 0.44; Comparative Fit Index (CFI) = 0.99; Tucker-Lewis Index (TLI) = 0.99; Root Mean Square Error of Approximation (RMSEA) = 0.007 (90% C.I. 0.000; 0.059). Conclusion GAD-7 has satisfactory psychometric properties. GAD-7 had significant correlations with the variables examined for construct validity with PSS and EPDS. GAD-7 is a reliable instrument for screening anxiety symptoms in perinatal period in research and clinical setting.